Kualitas Layanan Terpadu (Total Quality Service) Dalam Pendidikan - Syukri, Makmur; Sofian, Sopan (Jurnal Ilmiah Wahana Pendidikan, 2024)
Providing excellent and reliable service can increase client happiness, resulting in several benefits, including customer loyalty. However, gaining knowledge about quality and the desires of discerning consumers requires a significant investment of time and a comprehensive understanding process. The basic principle of TQS is to prioritize the effectiveness and efficiency of optimizing services. As nonprofit service organizations, educational institutions are institutions that offer services characterized by four distinct traits: intangibility, indivisibility, variability, and perishability. The customer identification framework for educational institutions consists of three components: 1. internal customers consisting of academic and administrative personnel, 2. direct external customers, and 3. indirect external consumers. Islam, like other religions, also sets guidelines for the Total Quality Service process. Therefore, by understanding the attributes and understanding the needs of clients, educational institutions aim to instill confidence that their services will effectively meet customer expectations and deliver delight.